Kampanye Pemilihan Umum Presiden dan Wakil Presiden Perspektif Fikih Siyâsah - Anis Hidayati (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2015)
Abstract: This article discusses about a Islamic political jurisprudence’s point of view againts campaign for president and vice president election. It is carried out based on Law No. 42 year 2008 concerning with the election of president and vice president. The general election campaign is a sovereign right of the people to produce democratic government based on Pancasila and the Constitution of the Republic of Indonesia (UUD) 1945. The implementation of the general election campaign has a positive effect that is beneficial for the candidates and for the publics to know the candidates they would choose to be a leader. In Islamic political jurisprudence’s perspective, the implementation of the general election campaign for president and vice president can realize the political rights of individuals associated with the right to nominate and the right to occupy a certain post. All of the people and citizens are entitled to gain a guarantee of their human rights (Hurriyah al-shakhsiyyah) before the law and government. Keywords: Campaign, general election, president, Islamic political jurisprudence.